PSIX-1 Associative effect of wet-distillers' grains plus solubles and tannin-rich peanut skin supplementation on in vitro rumen fermentation, greenhouse gas emissions, and microbiome changes. (5th December 2019) - Min, Byeng Ryel; Castleberry, Lana; Parker, David; Waldrip, Heidi; Brauer, David; Allen, Heather
Abstract: The role of tannin-rich peanut skin (PS) and associative effects of different levels of wet distillers' grains plus solubles (WDGS) on ruminal fermentation, microbial changes, and mitigation of greenhouse gas (GHG) and other emissions in bovine rumen fluid were investigated. All gases were collected using an Ankom in vitro system for methane (CH4 ), nitrous oxide (N2 O), and hydrogen sulfide (H2 S) analyses. Fifteen % ground PS against 0, 10, 20, 30, and 40 % DM of WDGS were used. RT-qPCR were conducted to determine microbial diversity. In the absence of PS, total CH4 and H2 S, or CH4 and H2 S productions per gram of DM substrate, were linearly increased (P < 0.05) with increasing WDGS. However, in the presence of PS, those trends were reversed and CH4 and H2 S productions were decreased (P < 0.05), suggesting that a diet with 15% PS and supplementation of 10 and 20% WDGS were able to reduce CH4 and H2 S emissions by 12 and 33%, respectively. In the presence of PS, rumen fermentation rate (as a measured by VFA) and acetate/propionate (A/P) ratio was decreased with increasing WDGS, with PS x WDGS interactions (P < 0.01). In the presence of PS, there was a decreased (P < 0.05) the average population of Bacteroidetes, total methanogens, Methanobrevibacter sp. AbM4, and total protozoa populations at 40% WDGS, with PS x WDGS interactions (P < 0.01). The population of total methanogens (R 2 = 0.57; P < 0.01), Firmicutes populations (R 2 = 0.46: P < 0.05), and F/B ratio (R2 = 0.46; P < 0.03) were strongly correlated with ruminal methane gas production. Therefore, associative effect of tannin-rich PS and WDGS suppressed methanogenesis pathways directly across their antimethanogenic activity and secondarily throughout their modification of protozoa population.